Ambiguity Aversion and the Absence of Wage Indexation. - Mukerji, S; Tallon, J (Department of Economics (University of Oxford), 2002)
This paper analyzes optimal wage contracting assuming agents are not subjective expected utility maximizers but are, instead, ambiguity (or uncertainty) averse decision makers who maximize Choquet expected utility. We show that such agents will choose not to include any indexation coverage in their wage contracts even when inflation is uncertain, unless the perceived inflation uncertainty is high enough. Significantly, the exercise does not presume any exogenous costs (e.g., transactions costs) of including indexation links.